2004
DOI: 10.1177/0310057x0403200610
|View full text |Cite
|
Sign up to set email alerts
|

Cost Calculation and Prediction in Adult Intensive Care: A Ground-up Utilization Study

Abstract: The ability of various proxy cost measures, including therapeutic activity scores (TISS and Omega) and cumulative daily severity of illness scores, to predict individual ICU patient costs was assessed in a prospective "ground-up" utilization costing study over a six month period in 1991. Daily activity (TISS and Omega scores) and utilization in consecutive admissions to three adult university associated ICUs was recorded by dedicated data collectors. Cost prediction used linear regression with determination (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 38 publications
6
27
0
5
Order By: Relevance
“…Moran et al ., also reported that the survivors and nonsurvivors in Australian ICUs had significantly different variances of the total overhead costs and length of ICU stay. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Moran et al ., also reported that the survivors and nonsurvivors in Australian ICUs had significantly different variances of the total overhead costs and length of ICU stay. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Cost data for ICU patient stay, including all related management activity, but excluding costs associated with provision of services external to the ICU, was generated from a 3‐month study (1991) in three South Australian adult ICUs; an in‐detail analysis of this data has recently been reported [13]; where separate predictive models for survivors and non‐survivors were presented. For all patients ( n = 1333) [13] recorded total (1991) mean (SD) patient costs per ICU episode as A$6801 (10 311) with ICU length of stay 3.9 (6.1) days; using standard inflation adjustments, mean calendar year 2002 costs were A$9343. The computed (2002) occupied ICU bed‐day costs at A$ 2395 were, as noted by Rechner & Lipman [14] quite similar to two recent studies: A$2670 for calendar year 2003 [14], from Australia, and approximately A$2400 for financial year 2000–01 [15], from the UK.…”
Section: Methodsmentioning
confidence: 99%
“…Im Unterschied dazu werden bei der Bottom-up-Methode sämtliche erbrachten Leistungen detailliert erfasst und dann monetär bewertet [11,12,13]. Notwendige Voraussetzung ist hier jedoch eine detaillierte Erfassung der Einzelleistungen.…”
Section: Trends Und Medizinökonomieunclassified